Considering sensory processing issues in trauma affected children: the physical environment in children’s residential homes - Christopher Robinson; Alicia Madeleine Brown (Scottish Journal of Residential Child Care)
Sensory processing issues are generally considered to be clinically significant in children who have suffered abuse and trauma and much has been written about the possible neurological correlates of such sensitivities (De Bellis and Thomas, 2003; van der Kolk, 2014). Comparatively little focus has been given to the functional aspects of these sensitivities, and particularly how these might interact, in context, with a child’s underlying neurological vulnerabilities. In this respect, the environment surrounding the child is a neglected area of significant, perhaps critical, importance. In terms of potential hypersensitivity to environmental stimuli, children with Autistic Spectrum Conditions (ASC), although with different aetiological correlates to trauma affected children, are known to face profound environmental challenges. Children with ASCs have received a wealth of attention in the literature with regard to these sensory challenges, whereas, in contrast, trauma affected children have received very little direct attention at all. It is the aim of this paper to focus on the environmental aspects of sensory processing in trauma affected children, specifically in relation to the physical environment of children’s residential homes.